Time trend in depression diagnoses among acute coronary syndrome patients and a reference population from 2001 to 2009 in Denmark. (3rd July 2016) - Jørgensen, Terese Sara Høj; Mårtensson, Solvej; Ibfelt, Else Helene; Jørgensen, Martin Balslev; Wium-Andersen, Ida Kim; Wium-Andersen, Marie Kim; Prescott, Eva; Osler, Merete
Abstract: Introduction In the last decade a range of recommendations to increase awareness of depression in acute coronary syndrome patients have been published. To test the impact of those recommendations we examine and compare recent time trends in depression among acute coronary syndrome patients and a reference population. Methods 87 218 patients registered with acute coronary syndrome from 2001–2009 in Denmark and a match reference population were followed through hospital registries and medication prescriptions for early (≤30 days), intermediate (31 days to 6 months) and later (6 months to 2 years) depression in the acute coronary syndrome population and overall depression in the reference population. Cox regression models were used to compare hazard ratios (HRs) for depression over calendar years. Results During the study period, 11.0% and 6.2% were diagnosed with depression in the acute coronary syndrome population and in the reference population, respectively. For the acute coronary syndrome population, the adjusted HRs increased for early (HR (95% CI) 1.04 (1.01–1.06)) and intermediate depression (HR (95% CI) 1.01 (1.00–1.03)), whereas the adjusted HRs did not change for later depression (HR (95% CI) 0.99 (0.98–1.00)). For the reference population the adjusted HRs for depression increased through the study period (HR (95% CI) 1.01 (1.01–1.03)). Conclusion Increase in diagnoses of depressions within 6 months of acute coronary syndrome may be explained by increased focus on depression in this patient group in combination with increased awareness of depression in the general population.